Commonwealth Caribbean diplomacy : a new strategy for the new world order. - Sutton, Paul (1992)
Comments on the record of Commonwealth Caribbean diplomacy to date, and considers some of the practical means by which the region might seek to adjust and improve its relations with Europe and North America during the rest of this decade. Offers some general thoughts on the changing nature of the diplomacy required of the region by the structure of the New World Order.